IL-15 promotes human myogenesis and mitigates the detrimental effects of TNFα on myotube development - O’Leary, Mary F.; Wallace, Graham R.; Bennett, Andrew J.; Tsintzas, Kostas; Jones, Simon W. (Nature Publishing Group, 2017)
Studies in murine cell lines and in mouse models suggest that IL-15 promotes myogenesis and may protect against the inflammation-mediated skeletal muscle atrophy which occurs in sarcopenia and cachexia. The effects of IL-15 on human skeletal muscle growth and development remain largely uncharacterised. Myogenic cultures were isolated from the skeletal muscle of young and elderly subjects. Myoblasts were differentiated for 8 d, with or without the addition of recombinant cytokines (rIL-15, rTNFα) and an IL-15 receptor neutralising antibody. Although myotubes were 19% thinner in cultures derived from elderly subjects, rIL-15 increased the thickness of myotubes (MTT) from both age groups to a similar extent. Neutralisation of the high-affinity IL-15 receptor binding subunit, IL-15rα in elderly myotubes confirmed that autocrine concentrations of IL-15 also support myogenesis. Co-incubation of differentiating myoblasts with rIL-15 and rTNFα, limited the reduction in MTT and nuclear fusion index (NFI) associated with rTNFα stimulation alone. IL-15rα neutralisation and rTNFα decreased MTT and NFI further. This, coupled with our observation that myotubes secrete IL-15 in response to TNFα stimulation supports the notion that IL-15 serves to mitigate inflammatory skeletal muscle loss. IL-15 may be an effective therapeutic target for the attenuation of inflammation-mediated skeletal muscle atrophy.